Biomedical waste management among healthcare workers in a Primary Health Centre in Sikkim, India-A KAP study - Sunita Thapa; Nasrin B. Laskar (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: "Biomedical waste (BMW) is the waste generated during the diagnosis, treatment or immunization of human beings or animals or research activities pertaining thereto or in the production or testing of biologicals" (Management and Handling Rules, 1998 of India). As it is a source of dangerous diseases, the handlers need to have adequate knowledge about the same. MATERIALS AND METHODS: This study assessed the knowledge, attitude, and practice of biomedical waste management among healthcare workers in a Primary Health Centre and tested the association between KAP and selected variables. For this study, one PHC among six in Sikkim was purposively selected and all health providers attached with the PHC were assessed for KAP toward BMW Management. Data was summarized using SPSS version 27. Pearson's Chi-square test (or Fisher's exact test) was applied to find the association between KAP and selected variables (P < 0.05 was considered significant). Bivariate and multivariate logistic regression analysis was performed for the significant variables. RESULTS: The mean age of the study participants ranged from 36.42 ± 8.983 years. 66%, 66%, and 60% of healthcare workers had adequate knowledge scores, favorable attitude scores, and good practice scores in BMWM, respectively. CONCLUSION: A knowledge gap was observed among the supportive medical staff as there was a lack of formal training in BMWM. Training of not only medical officers but also for waste handlers should be conducted at the time of appointment as well as refresher trainings should be done for the overall health and safety of all waste handlers.